2002
DOI: 10.1021/ma011860i
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of the Thermochromic Transition in Urethane-Substituted Polydiacetylenes

Abstract: Thermochromic transitions of the polydiacetylenes (PDAs) of the bis(ethyl)-and bis-(isopropyl)urethanes of 5,7-dodecadiyne-1,12-diol (poly(ETCD) and poly(IPUDO)) were investigated by solid-state 13 C cross-polarization and magic angle spinning (CP/MAS) nuclear magnetic resonance (NMR) spectroscopy and differential scanning calorimetry (DSC). Side group conformational changes resulting from the polymerization and thermochromic transition were monitored by solid-state 13 C CP/MAS NMR. Consecutive heating/cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 45 publications
(92 reference statements)
2
83
0
Order By: Relevance
“…It is known that the phasetransition of PDA is taken place by the strain of the backbone owing to the reorientation of the side chains. [11] Therefore, we may expect that the optical induced chirality we study here will also be dependent on the strain of backbone. Interestingly, our previous study showed that the thermochromic phase transition never broke the chirality of PDA induced by CPL, [6] and topochemical reaction was probable at high substrate temperature.…”
Section: Uv-vis Absorption and CD Spectrummentioning
confidence: 88%
“…It is known that the phasetransition of PDA is taken place by the strain of the backbone owing to the reorientation of the side chains. [11] Therefore, we may expect that the optical induced chirality we study here will also be dependent on the strain of backbone. Interestingly, our previous study showed that the thermochromic phase transition never broke the chirality of PDA induced by CPL, [6] and topochemical reaction was probable at high substrate temperature.…”
Section: Uv-vis Absorption and CD Spectrummentioning
confidence: 88%
“…It was suggested that the change in the conformation of the conjugated ene-yne backbone or the conjugated p-orbital arrays (from planar to partially distorted) varied the conjugation length, which was primarily responsible for the color change of the polydiacetylenes. [36][37][38][39] Regarding factors affecting conformation change in the π-bond, head group interactions, arising from hydrogen bonds/lateral stacking between aromatic rings or the flexibility of head groups, were suggested to play important roles. 30,[33][34][35]40 Meanwhile, melting of the unreacted monomers was also suggested to be a factor for the conformation change of the backbone.…”
Section: -35mentioning
confidence: 99%
“…When oleic acid are added, the disruption of hydrogen bonding and π-π stacking formation can allow the release of the strain energy imposed on the alkyl side chains generated during polymerization. 12 The release of side-chain strain can cause partial distortion of the arrayed p orbitals, which can lead to the observed change in optical properties. Both anionic head group and appropriate long hydrophobic moiety are required.…”
Section: Notesmentioning
confidence: 99%